Maturation of speech-elicited event-related potentials from birth to 28 months: Typical development with minor effects of dyslexia risk - Navarrete-Arroyo, Sergio; Putkinen, Vesa; Kujala, Teija; Virtala, Paula (Elsevier BV, 2025)
This study investigated in a longitudinal setting the maturation of obligatory auditory event-related potentials (ERPs) during infancy and early childhood, comparing the developmental patterns in infants with or without a familial risk of dyslexia. To that end, we recorded ERPs to repetitive speech sounds at birth, 6 months, and 28 months in a sample of ∼200 children over-represented by children at risk for developmental dyslexia. Additionally, we assessed the impact of a music listening intervention on these ERPs. We found that infant P1 and N2 are the most robust ERPs during the first years of life. A distinct, broad infant P1 response was observable already at birth, with a infant P1-N2 pattern emerging by 6 months. Infant P1 amplitude increased from birth to 6 months, whereas its latency decreased from birth to 28 months. Infant N2 latency increased between 6 and 28 months, with no significant changes in amplitude. The control group without familial dyslexia risk exhibited smaller infant N2 amplitudes than the at-risk group at 6 months. No effects of the infant music listening intervention on the ERPs were seen. These results, with a large sample size and longitudinal setting, reflect auditory development, serving as a reference for future studies including clinical groups.
Keywords: Developmental dyslexia; Event-related potentials; Music intervention; N2; Neural speech encoding; P1.